Comparison of the resistance to cyclic fatigue of One Curve, One Shape, 2Shape and EdgeFile X3 files in simulated single and S-shaped (double) curvatures - Adıgüzel, Mehmet; Öztekin, Faruk (My University, 2020)
Aim: To evaluate the fracture resistance to cyclic fatigue of One Curve (Micro Mega, Besancon, Cedex, France), One Shape (Micro-Mega), 2Shape (Micro-Mega) and EdgeFile X3 (EdgeEndo, Albuquerque, NM) files in simulated root canals. Methodology: One hundred and sixty nickel-titanium endodontic files were tested in simulated canals with single and s-shaped (double) curvatures. The One Curve (25/.06), One Shape (25/.06), 2Shape (25/.06) and EdgeFile X3 (25/.06) files were assessed (n=20 for each test). All the files were rotated up to fracture occurred. The number of cycles to fracture (NCF) was determined and also, the length of the fractured file part was measured. For statistical analysis, one-way analysis of variance and Tukey HSD tests were used (p < 0.05). Results: NCF for all instrument groups were significantly higher in the single curvature canal compared to the s-shaped curvature canal (p < 0.05). The EdgeFile X3 had the highest fatigue resistance in both curvature groups. The NCF of the One Curve were higher than that of the One Shape and 2Shape files (P < 0.05). In the s-shaped curvature canal, the files inclined to fracture more often in the apical curvature compared to the coronal curvature. There was no statistically considerable difference in the length of the fractured parts among the four experiment groups in either the single or s-shaped canal curvatures (p > 0.05). Conclusion: Within the limitations of this study, fracture resistance to cyclic fatigue was the highest for the EdgeFile X3 group followed by the One Curve group and lowest for the 2Shape and One Shape group.
Keywords: Diş Hekimliği